Analysis of the subcellular localization and function of Î²-tubulin isotypes in two single-cell model systems: Tetrahymena thermophila and Euplotes focardii - SPARVOLI, Daniela (Università degli Studi di Camerino, 2013)
To illustrate the results I obtained during my PhD course in a simple and clear way, I decided to organize my PhD thesis in the following way: a general introduction about the main topic of my research work and a brief description of the ciliated protozoa Tetrahymena thermophila and Euplotes focardii, the two cell model systems I used in this study. Subsequently, I reported the two manuscripts one to be submitted, ''Tubulin isotypes and cellular function: the EFBT3 tubulin isotype from the Antarctic ciliate Euplotes focardii is involved in the formation of microtubule with low turnover'', and one published in PLoSone journal in 2012, ''Distinct functional roles of Î²-tubulin isotypes in microtubule arrays of Thetrahymena thermophila, a model single-celled organism'', where the majority of my results are described. The last part of my thesis is focused on most recent data obtained from the analysis of Î²-tubulin mutants in Thetrahymena thermophila and they will be included in a new scientific paper.